2023
DOI: 10.3126/jhp.v11i1.61206
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Primary Caregivers’ Feeding Habits on the Nutrition Status of Pre-schoolers in Rupandehi District of Nepal

Prakash Sharma,
Chitra Bahadur Budhathoki

Abstract: Healthy food habits of primary caregivers may contribute to the overall growth, development, and optimal health of the ppreschoolers. This quantitative research aimed to examine the impact of the feeding practices of caregivers on nutritional status of 384 preschoolers (aged 36-71 months) in Rupandehi District of Nepal. The effects of feeding habit were compared with the nutritional status and thus the impact was examined. Information regarding socio-economic standing, demographics, feeding habits, and childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Parents' nutritional knowledge undeniably plays a pivotal role in shaping children's dietary habits and physical activity (Woźniak et al, 2022;Adamo & Brett., 2014). A cross-sectional study conducted in Nepal revealed that caregivers' educational level and economic background significantly impacted the health status of schoolchildren, with recommendations for improvement emphasizing the active involvement of parents (Sharma & Budhathoki, 2023). In the Jhaukhel-Duwakot region (Note 2), nearly all assessed children exhibited fair nutrition practice, and the children's dietary and physical scores increased with their mothers' higher levels of education (Oli et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Parents' nutritional knowledge undeniably plays a pivotal role in shaping children's dietary habits and physical activity (Woźniak et al, 2022;Adamo & Brett., 2014). A cross-sectional study conducted in Nepal revealed that caregivers' educational level and economic background significantly impacted the health status of schoolchildren, with recommendations for improvement emphasizing the active involvement of parents (Sharma & Budhathoki, 2023). In the Jhaukhel-Duwakot region (Note 2), nearly all assessed children exhibited fair nutrition practice, and the children's dietary and physical scores increased with their mothers' higher levels of education (Oli et al, 2018).…”
Section: Introductionmentioning
confidence: 99%